STUDI KOMPARATIF MINAT BELAJAR SISWA PADA KELUARGA DEMOKRATIS DAN OTORITER - Qamariyatul, Sitti (Pusat Penelitian dan Pengabdian kepada Masyarakat STKIP Citra Bakti, 2025)
This study aims to describe students' learning motivation in terms of parenting styles that are free demo for parents. Motivation has a very significant role in determining the results of the learning process. Motivation is something that can affect student learning outcomes. This research is a type of qualitative descriptive research. The data collection technique used was observation and interview. The informants in this study were students of the SMK As-Salafiyah Sumberduko Pamekasan. The results show that the findings obtained in this study, where the hypothesis has been tested and tested in learning, the following research can be carried out: Motivation to learn from democratic parenting is high category.